Infinitude in The Qur’an: A Rhetorical-Rational Approach to Qur’anic Exegesis - Ahmad Najib; Mekki Klaina (Darul Yasin Al Sys, 2026)
This study explores the concept of infinitude in the Qur’an from a rhetorical–rational perspective, emphasizing its significance for understanding the text and its theological and intellectual dimensions. Its importance lies in presenting, for the first time, an integrated treatment of infinitude within Qur’anic discourse, thereby uncovering foundational aspects central to creed and offering exegetical implications that enrich both method and interpretation. The research problem arises from the absence of comprehensive studies that combine rhetorical analysis with rational reasoning in tafsīr, a gap that has at times led to literalist readings or interpretations that appear to conflict with Islamic theological principles. Employing an inductive methodology, the study collects relevant verses, examines them through tafsīr and Qur’anic sciences, and analyzes them in dialogue with the views of exegetes and theologians to refine meanings and intentions. The findings reveal three main contributions. First, six principal themes of infinitude in Allah’s attributes are identified: pre-eternity and everlastingness, comprehensiveness of knowledge, absoluteness of power, transcendence beyond limit and place, vastness of mercy, and the comprehensive negation of all forms of limitation. Second, the Qur’an presents infinitude across three dimensions: divine attributes, eschatological realities such as the eternity of Paradise and Hell, and the discourse of obligation that magnifies divine words, blessings, and warnings. Third, the study underscores the necessity of integrating rhetorical and rational methodologies, as reliance on literal wording alone risks anthropomorphism or apparent contradiction, whereas a combined rhetorical–rational approach safeguards divine transcendence and clarifies the intended meaning.